(untitled) (KYAMC Journal, 2017)
A total of 12,798 fungal diseases patients were interviewed about their socio-demographic characteristics attending the Skin and V.D. department of Rajshahi Medical College Hospital from July 2002 to June 2004. It was found that high prevalence of diseases was in age group 20-29 years (36.03%) and females were the more suffered group (55.39%) than the males (44.61%). Among the different occupations, housewives ranked first (37.05%) and shows a definite association with fungal infections due to sweating (P<0.001). Tinea corporis were highest in prevalence (36.48%) as compared to other clinical varieties of diseases. Majority of the patients were heavy sweating group (71.15%). It was showed that patients who washed their cloths and bed sheets within seven days were less suffered group (7.89%).The illiterate group of patients was highly sufferer (51.07%) and unawareness shows a definite association with fungal diseases (P<0.001). It was observed that low-income group of people had the highest number of diseases (59.45%) than the higher income group of patients (12.04%). KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 380-385